2020
DOI: 10.21595/jme.2020.21847
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of fuel consumption and harmful emissions of cars when using different types of fuel

Abstract: The article presents the results of studies of energy, environmental and fuel efficiency indicators of a passenger car with a gasoline injection system. The engine is equipped with a device additionally supplying liquefied petroleum gas (LPG) and it has an ignition timing variator (ITV). As a result of research, an improvement in the fuel efficiency of a car in thermal equivalent was found when the engine was running on LPG and a slight increase in energy performance was observed. Emissions of pollutants with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The calculation of emissions in the air from agricultural machinery is based on [32]. Only the most relevant types of exhaust gases according to the existent literature were calculated [38,39].…”
Section: Direct Emissionsmentioning
confidence: 99%
“…The calculation of emissions in the air from agricultural machinery is based on [32]. Only the most relevant types of exhaust gases according to the existent literature were calculated [38,39].…”
Section: Direct Emissionsmentioning
confidence: 99%
“…This means that these items may directly or indirectly collect, process and/or exchange data via a computer network and the Internet. Concurrently, other growing trends on a global scale are the advances in electromobility [2][3][4][5][6][7][8][9], obtaining energy from renewable sources and alternative fuels [10][11][12][13][14][15][16] and reducing exhaust emissions from means of transport [17][18][19][20][21][22][23][24]. The analysis of the literature and the state of knowledge confirmed that there are many technologies on the market for obtaining data from photovoltaic systems, electric car chargers and electricity meters taken from the power grid [2,25,26].…”
Section: Introductionmentioning
confidence: 99%